Sero-Epidemiological Study of Varicella in the Italian General Population - Giovanni Gabutti; Tiziana Grassi; Francesco Bagordo; Marta Savio; Maria Cristina Rota; Paolo Castiglia; Tatjana Baldovin; Francesco Napolitano; Alessandra Panico; Matilde Ogliastro; Claudia Maria Trombetta; Savina Ditommaso; et al. (Vaccines, 2023)
The aim of this study was to analyze the seroprevalence of varicella in Italy and to evaluate the impact of varicella vaccination, which has been mandatory for newborns since 2017. The levels of VZV-specific IgG antibodies were determined by the ELISA method in residual serum samples obtained from subjects aged between 6 and 64 years and residing in 13 Italian regions. Overall, 3746 serum samples were collected in the years 2019 and 2020. The overall seroprevalence was 91.6% (89.9% in males and 93.3% in females; p = 0.0002). Seroprevalence showed an increasing trend (p < 0.0001) starting in the younger age groups: 6–9 years: 84.1%; 10–14 years: 88.7%; 15–19 years: 89.3%; 20–39 years: 93.1% and >40 years: 97.0%. The seroprevalence data obtained in the present study were compared with those relating to previous sero-epidemiological surveys conducted, respectively, in the years 1996–1997, 2003–2004 and 2013–2014, taking into consideration only data from regions monitored in all surveillance campaigns. The comparison highlighted for the period 2019–2020 showed significantly higher values in the age groups 6–9 (p < 0.001), 10–14 (p = 0.018) and 15–19 years (p = 0.035), while in adults, the trend did not change over time (ns). These results highlight the positive impact of varicella vaccination in Italy.